Role of Various Laws in Prison Administration and Improving Conditions of Women under Trials in India: Exploring the Impact of Laws on Prison Administration and Women's Rights in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Human rights in simple language may be categorized as the Fundamental Rights to which every man or woman living in any part of the world is entitled by virtue of having been born as a human being, the rights that are required for the full and complete development of human personality. Human rights are derived from the dignity and worth inherent in human person. The Courts in India have been recognizing and enforcing the human rights as natural rights of mankind or as Constitutional mandates or as rights of an Indian in an Independent policy.[1] An important organ of the criminal justice administration of any State is the prison. It is an institution where persons convicted of major crimes or felonies are deprived of their liberty for the purpose of reformation. However, practical experience suggests that prisons are factories where criminals are made owing to regular perpetration of State crime.